101 Ways to Promote Your Web Site - Sweeney, Susan (Maximum Press, 2012)
With hundreds of proven tips, tools, and techniques, this freshly updated edition explains how to make the most of the latest Web 2.0 trends and techniques such as RSS, blogs, podcasting, and mobile marketing for online success.